Major Depression Diagnoses Among Patients With Systemic Sclerosis: Baseline and One‐Month Followup. Issue 3 (March 2015) - Thombs, Brett D.; Jewett, Lisa R.; Kwakkenbos, Linda; Hudson, Marie; Baron, Murray; the Canadian Scleroderma Research Group
<x xml:space="preserve">Abstract</x> Objective Depression is common in many rheumatic diseases and is associated with poor prognosis. No studies of patients with any rheumatic diseases, however, have assessed the stability of major depressive disorder (MDD) diagnoses over time. The objective of the present study was to assess the stability of MDD diagnoses among patients with systemic sclerosis (SSc; scleroderma), a rare autoimmune rheumatic disease, across 2 assessments approximately 1 month apart. Methods SSc patients were recruited from 7 Canadian Scleroderma Research Group Registry sites (April 2009 to June 2012). Current (30‐day) MDD was assessed with the Composite International Diagnostic Interview at baseline and approximately 1 month later. Results Among 309 patients with baseline assessments who received followup assessments an average of 34 days later, prevalence of 30‐day MDD was 4% (95% confidence interval [95% CI] 2%–7%; n = 12) at baseline and 5% (95% CI 3%–8%; n = 16) at followup. Only 3 of 12 patients (25% [95% CI 9%–53%]) with MDD at baseline had MDD 1 month later. Conclusion Most patients with SSc who meet criteria for MDD appear to experience mild, time‐limited episodes of low mood that often resolve on their own without specific treatment. Consistent with international guidelines on depression management in nonpsychiatric settings, "watchful waiting" or "active monitoring" is a good strategy for SSc patients with mild depression to avoid unnecessary treatment among those whose symptoms may be transient and may resolve without medical intervention.